2019
DOI: 10.1097/fjc.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Late Phases of Cardioprotection During Remote Ischemic Preconditioning and Adenosine Preconditioning Involve Activation of Neurogenic Pathway

Abstract: Background: The role of the neurogenic pathway in early phases of cardioprotection during remote ischemic preconditioning (RIPC) and adenosine preconditioning is reported. Aim: This study was designed to explore the involvement of the neurogenic pathway in late phases of cardioprotection during RIPC and adenosine preconditioning. Material and Methods: Fifty-four Wistar rats were used and divided into 9 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…an early phase (first window) and late phase (second window) [3,35]. These observations of the present study documenting the myocardial injury in response to ischemia and reperfusion along with the cardioprotective effects of the late phase of remote preconditioning are in accordance with the previously published studies [4,36]. Moreover, the present study results document that the cardioprotective effects of the late phase of remote preconditioning were significantly attenuated in old rats.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…an early phase (first window) and late phase (second window) [3,35]. These observations of the present study documenting the myocardial injury in response to ischemia and reperfusion along with the cardioprotective effects of the late phase of remote preconditioning are in accordance with the previously published studies [4,36]. Moreover, the present study results document that the cardioprotective effects of the late phase of remote preconditioning were significantly attenuated in old rats.…”
supporting
confidence: 93%
“…Hydrogen sulfide restores cardioprotective effects of remote ischemic preconditioning in aged rats via HIF-1/Nrf2 signaling pathway that the late phase of remote preconditioning confers a higher magnitude of cardioprotection than the early phase [3,4].…”
Section: Original Articlementioning
confidence: 98%
“…Such four alternate cycles of ischemia and reperfusion to the hind limb constituted remote preconditioning. After 24 h, the rats were sacrificed to isolate hearts, which were perfused on the Langendorff apparatus 3 .…”
Section: Remote Ischemic Preconditioning (Rip)mentioning
confidence: 99%
“…Apart from short term effects of diabetes, long-standing uncontrolled hyperglycemia in diabetes produces a number of complications, including increase in the tendency to develop ischemia-reperfusion induced myocardial injury 1,2 . Remote preconditioning a therapeutic strategy in which short episodes of ischemia and reperfusion to an organ other than heart (nontarget or remote organ) confers protection to heart from sustained ischemia-reperfusion injury 3 . This therapeutic strategy has been used in preclinical as well in clinical setup to confer protection to heart against ischemiareperfusion injury 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Murry et al [ 16 ] put forward the concept of ischemic preconditioning (IPC) in 1986, which suggests that the short-term reperfusion of ischemic myocardium can significantly improve myocardial I/R injury. Many studies have shown that IPC can be used to alleviate I/R injury of various tissues and organs in many animals [ 17 19 ]. However, the clinical value of IPC is limited because it is difficult to estimate the time of ischemia of tissues and organs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%